Experimental Analyses Emphasize the Stability of the Meisenheimer Complex in a SNAr Reaction Toward Trends in Reaction Pathways - Campodónico, Paola R.; Olivares, Belén; Tapia, Ricardo A. (Frontiers in Chemistry, 2020)
The mechanism of SNAr reactions between 2-chloro-5-nitropyrimidine with primary and secondary alicyclic amines, respectively have been studied by kinetic measurements. The kinetic data obtained in aqueous media opens a controversial discussion based on Bronsted-type plots analysis. The first approach based on the kinetic data reveals a non-catalyzed pathway. Then, the subtlety of the mathematical treatment of the kinetic data is discussed over a concerted or stepwise mechanism, respectively.